Carbon Nanohorns as Integrative Materials for Efficient Dye‐Sensitized Solar Cells. (29th August 2013) - Costa, Rubén D.; Feihl, Sebastian; Kahnt, Axel; Gambhir, Sanjeev; Officer, David L.; Wallace, Gordon G.; Lucio, María Isabel; Herrero, María Antonia; Vázquez, Ester; Syrgiannis, Zois; Prato, Maurizio; Guldi, Dirk M.
<x xml:space="preserve">Abstract</x> Different nanocarbons, that is, single‐wall carbon nanotubes, graphene, single‐wall carbon nanohorns (SWCNHs), and their respective oxidized analogs have been used to fabricate novel doped TiO2 electrodes for DSSCs. Our results indicate that all of the nanocarbons significantly enhance the device characteristics when compared to standard TiO2 electrodes. Overall, our most outstanding finding is that SWCNH derivatives are also a plausible material for developing highly‐efficient DSSCs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>